Biblical commentary on the Old Testament - Keil, Carl Friedrich (Eerdmans, 1900)
[Bk.1-5,3v.]: The Pentateuch / C.F. Keil and F. Delitzsch ; tr. by James Martin -- [Bk.6-8]: Joshua, Judges, Ruth / C.F. Keil and F. Delitzsch ; tr. by J. Martin -- [Bk.9-10]: Biblical commentary on the books of Samuel / C.F. Keil and F. Delitzsch ; tr. by J. Martin -- [Bk.11-12]: The books of the Kings / C.F. Keil ; tr. by J. Martin -- [Bk.13-14]: The books of the Chronicles / C.F. Keil ; tr. by Andrew Harper -- [Bk.15-17]: The books of Ezra, Nehemiah, and Esther / C.F. Keil ; tr. by Sophia Tucker -- [Bk.18,2v.]: Biblical commentary on the book of Job / F. Delitsch ; tr. by Francis Bolton -- [Bk.19,3v.]: Biblical commentary on the Psalms / F. Delitsch ; tr. by F. Bolton -- [Bk.20,2v.]: Biblical commentary on the Proverbs of Solomon / F. Delitsch ; tr. by M.G. Easton -- [Bk.21-22]: Commentary on the Song of Songs and Ecclesiastes / F. Delitsch ; tr. by M.G. Easton -- [Bk.23,2v.]: Biblical commentary on the prophecies of Isaiah / F. Delitsch ; tr. by J. Martin -- [Bk.24-25,2v.]: The prophecies of Jeremiah [and] The Lamentations of Jeremiah / C.F. Keil ; tr. by David Patrick and James Kennedy -- [Bk.26,2v.]: Biblical commentary on the prophecies of Ezekiel / C.F. Keil ; tr. by J. Martin -- [Bk.27]: Biblical commentary on the book of Daniel / C.F. Keil ; MGE -- [Bk.28-39,2v]: The Twelve Minor Prophets / C.F. Keil ; tr. by J. Martin.